Зубчатые передачи редукторов с профильно-продольной модификацией зубьев - Спицын, В. Е.; Романов, В. В.; Дейнекин, А. С.; Мироненко, А. И. (Eastern-European Journal of Enterprise Technologies, 2009)
The paper presents main calculation results of gearings with teeth point-contact engagement system, having high load-carrying capacity, improved weight and overall dimensions and vibrational and acoustic performance. Methods of static and dynamic tests of the aforementioned gearings are represented